1884 N.Y. Laws 46, ch. 46, § 7 - (:unkn) unknown (General Publisher, 1884)
Prohibited the sale or giving of any pistol or firearm to minors under the age of 18. Violators guilty of a misdemeanor.
--
Keywords: TRANSFER - MINORS